Effects of reciprocal cross on major characters and yield of two sweet-waxy corn (Zea Mays L.) Varieties - Ning, Xilin; Chen, Rei; Jiang, Long; Wu, Nan; Yang, Baiming; Xu , Ying; Wang , Mingkun (Bangladesh Journal of Botany, 2023)
Two sweet-waxy corn inbred lines, Jikenuo 20 and Wannuo 2000, were used as experimental materials. A randomized block experiment was conducted to analyze the differences and similarities in plant traits, ear traits, yield, appearance quality and main cooking quality between the two sweet-waxy corn varieties. Results showed that there were no significant differences in most plant traits, ear traits and yield between the two sweet-waxy corn varieties, indicating that the inheritance of the nucleus was dominant. There were some differences in the resistance and some cooking quality of the two sweet-waxy corn varieties in the reciprocal cross combinations, which indicated that the above characters were affected by cytoplasmic inheritance to a certain extent. Bangladesh J. Bot. 52(2): 625-630, 2023 (June) Special